Death comes to Kurland Hall - Lloyd, Catherine, 1963- (Lloyd, Catherine, 1963- Kurland St. Mary mystery., 2015)
Returning to Kurland St. Mary to help with a friend's wedding, Lucy Harrington is dismayed at the presence of Major Robert Kurland, but calls a truce with him when Mrs. Chingford, a meddling widow who had set her sights on Lucy's father, is found dead at the bottom of a staircase.